The Role Of Personnel To Improve Admin Performance In Providing Services To Consumers (at PT. Es Bagus Bengkulu City) - Fitria Asyifa; Nabillah Garnida; Suganda Firas Pratama; Fingki Ardiansa; Ade Kurniawan; Yulius Wahyu Setiadi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the role of personnel to improve admin performance in providing services to consumers of PT. Good Ice Bengkulu City. Researchers used qualitative research with a qualitative descriptive approach. Data collection was carried out using observation, interviews and documentation. Informants in this study were employees of PT. Es Bagus Bengkulu City which consists of Ka. Finance. Cashier, Ka. Production, Head of Warehouse and Personnel. The results of this study can be concluded that the role played by personnel managers in improving admin performance is in accordance with various functions of management including planning, organizing to dismissal. For training, the company has not been able to carry out independent training. From its inception until now PT. Es Bagus Bengkulu City does not make it directly but uses tools/machines to produce this ice. That way the number of employees working at PT. Es Bagus Bengkulu City only has 16 employees. Implementation of management functions as well as possible in managing employees and facilitating the realization of organizational goals and success.